Low cycle fatigue, creep and creep-fatigue interaction behavior of a TiAl alloy at high temperatures. (February 2018) - Dong, Chengli; Yu, Huichen; Jiao, Zehui; Kong, Fantao; Chen, Yuyong
Abstract: The creep-fatigue interaction (CFI) tests of a TiAl alloy were carried out at 750 °C and 800 °C in air to investigate the effect of dwell time on fatigue life. The low cycle fatigue (LCF) and creep tests were also conducted for comparison. The life to failure decreased with increasing dwell time and decreased with increasing minimum strain rate. Two life models based on dwell time and minimum strain rate were proposed to predict LCF, creep and CFI life, and the predicted life of both life models agrees very well with the tested life of the alloy at high temperatures. Graphical abstract: (a) Evolution of the mean strain with the cyclic time increasing under different dwell times at 750 °C; (b) Evolution of the mean strain with the cyclic time increasing under different dwell times at 800 °C. (c) Normalized time to failure ( T f / T f − LCF ) vs. effective dwell time (△t/tp ) at 750 °C and 800 °C; (d) Comparison between predicted life by Model I and tested life. (e) Normalized time to failure (Tf /Tf-creep ) vs. normalized minimum strain rate ( ε ̇ min / ε ̇ min, creep ) at 750 °C and 800 °C; (f) Comparison between predicted life by Model II and tested life.